ANALYSIS OF THE HATI SUHITA NOVEL BY KHILMA ANIS: RELIGIOUS ASPECTS OF HUMAN RELATIONS WITH SELF - Ilmu Hamimah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
Becoming a perfect human is something that cannot happen in the world. However, being a human being who strives and is determined to be perfect is something that can be achieved with all the conviction of the heart and requests for straightness on the path of Alah SWT. accompanied by self-effort towards true goodness. This can be referred to as the religious dimension of one's self to oneself. Instilling a strong religious character and heart readiness to go to the right path. The power of religious character over oneself can be applied in a variety of circumstances. Like being happy, sad, disappointed, impressed or so on. This situation really proves how much a person uses a religious attitude towards oneself. The following article contains several pieces of religious attitudes towards oneself that can add to our insight into this dimension of attitude.